Therapeutic effect of Jinzhen oral liquid for hand foot and mouth disease: a randomized, multi-center, double-blind, placebo-controlled trial. - Jun Liu; Guo-Liang Zhang; Gui-Qin Huang; Li Li; Chun-Ping Li; Mei Wang; Xiao-Yan Liang; Di Xie; Chang-Ming Yang; Yan Li; Xiu-Rong Sun; Hong-Sen Zhang; et al. (PLoS ONE, 2014)
BACKGROUND: No specific antiviral agent against hand foot and mouth disease (HFMD) is available for clinical practice today. OBJECTIVE: To evaluate the efficacy and safety of Jinzhen oral solution in treating uncomplicated HFMD. METHODS: In this randomized, double-blind, placebo-controlled trial, 399 children aged 1 to 7 years with laboratory confirmed HFMD were randomized to receive Jinzhen oral liquid or placebo 3 times daily for 7 days with a 3-day follow-up. The primary outcomes were time to the first disappearance of oral ulcers and vesicles on hand or foot and time to the first normalization of temperature (fever clearance). RESULTS: There were 199 children enrolling into the Jinzhen group including 79 with fever and 200 into the placebo group including 93 with fever. Jinzhen reduced the time to the first disappearance of oral ulcers and vesicles on hand or foot to 4.9 days (95% CI, 4.6 to 5.2 days), compared with 5.7 days (95% CI, 5.4 to 6.0 days) in the placebo group (P = 0.0036). The median time of fever clearance was shorter in the 79 children who received Jinzhen (43.41 hrs, 95% CI, 37.05 to 49.76) than that in the 93 children who received placebo (54.92 hrs, 95% CI, 48.16 to 61.68) (P = 0.0161). Moreover, Jinzhen reduced the risk of symptoms by 28.5% compared with placebo (HR, 0.7150, 95% CI, 0.5719 to 0.8940, P = 0.0032). More importantly, treatment failure rate was significantly lower in the Jinzhen group (8.04%) compared with that in the placebo group (15.00%) (P = 0.0434). The incidence of serious adverse events did not differ significantly between the two groups (9 in Jinzhen group vs. 18 in placebo, P = 0.075). CONCLUSIONS: Children with HFMD may benefit from Jinzhen oral liquid treatment as compared with placebo. TRIAL REGISTRATION: Chinese Clinical Trial Registry (http://www.chictr.org/en/) ChiCTR-TRC-10000937.